Examining Formative Assessment Practices in Mathematics in Primary Schools: China and Tanzania Comparative review - Kadau, Ibrahimu; Mallya, Asha Mussa (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2023)
Evaluation plays an enormous role in the teaching and learning process. Being aware of this, both China and Tanzania use formative assessment to meet the ‎requirements of competence-based curricula especially in mathematics at primary school level. ‎Therefore, the purpose of this study was to look into the formative assessment practices, nature, ‎challenges in mathematics used by Chinese and Tanzanian primary schools. This report used ‎documentary analysis to consult articles, dissertations, and books found in different electronic ‎journals such as ERIC and Science Direct and deem them to have suitable information for the ‎study. The report found that evaluation methods such as test, assignments, homework, and ‎projects are common in both countries. Moreover, some dissimilar is some form of assessment ‎including terminal test and monthly test which are common in Tanzania. Furthermore, bustling ‎classes, heavy teaching loads, and a lack of clarity on the formative assessment implementation ‎strategies have similarly contributed to the ineffective formative assessment in both countries. ‎Further, the researcher recommends the recruitment of mathematics teachers and the provision of ‎in-service and pre-service training to the teachers to reduce ineffectiveness in the implementation ‎of formative assessment in Chinese and Tanzanian primary schools.‎